Impact of Individual Characteristics and Democratic Leadership Style on Burnout in Nurses at Muhammadiyah Hospital in Sidoarjo, Indonesia - Ayunita Dewi (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims to determine the work environment, individual characteristics, job characteristics, and democratic leadership style Burnout on nurses at Siti Khodijah Hospital. This research includes quantitative research with hypothesis testing. The sample used in this study were 66 nurses at Siti Khodijah Hospital. The analytical tool used in this research is multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classic assumption test using SPSS version 18 for windows. Primary data in this study were obtained from questionnaires whose measurement used a Likert scale that was tested for validity and reliability. The results of this study prove that the work environment, individual characteristics, job characteristics, and democratic leadership style simultaneously influence Burnout. work environment has a partial effect on Burnout, individual characteristics have a partial effect on Burnout., job characteristics have a partial effect on Burnout. democratic leadership style also partially influences Burnout. and for the variable that has the most significant effect on Burnout. At the Nurse at Rs. Siti Khodijah Muhammadiyah Branch Throughout the work environment.